2007
DOI: 10.1086/512101
|View full text |Cite
|
Sign up to set email alerts
|

The 2004-2006 Outburst and Environment of V1647 Ori

Abstract: We studied the brightness and spectral evolution of the young eruptive star V1647 Ori during its recent outburst in the period 2004 FebruaryY2006 September. We performed a photometric follow-up in the bands V, R C , I C , J, H, and K s , as well as visible and near-IR spectroscopy. The main results derived from combining our data with those published by other authors are as follows: the brightness of V1647 Ori stayed more than 4 mag above the preoutburst level until 2005 October, when it started a rapid fading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
59
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 43 publications
14
59
3
Order By: Relevance
“…3, right) shows that not only the colors, but also the magnitude changes follow the reddening path, suggesting the same ΔA V ≈ 20 mag. This is different from what was observed for V1647 Ori, where the color changes were consistent with reddening, but the magnitudes required additional color-independent flux changes as well (Acosta-Pulido et al 2007). …”
Section: Color−color and Color−magnitude Diagramscontrasting
confidence: 82%
See 3 more Smart Citations
“…3, right) shows that not only the colors, but also the magnitude changes follow the reddening path, suggesting the same ΔA V ≈ 20 mag. This is different from what was observed for V1647 Ori, where the color changes were consistent with reddening, but the magnitudes required additional color-independent flux changes as well (Acosta-Pulido et al 2007). …”
Section: Color−color and Color−magnitude Diagramscontrasting
confidence: 82%
“…We observed V2492 Cyg with the LIRIS instrument installed on the 4.2 m William Herschel Telescope (WHT) at the Observatorio del Roque de Los Muchachos (Spain). The description of the instrument can be found in Acosta-Pulido et al (2007). On 2011 July 21/22 JHK S images were taken, while on 2011 August 1/2 long-slit intermediate resolution spectra in the ZJ and HK bands were obtained.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, 2003 outburst lasted for a total of ∼ 2 years and V1647 Ori returned to its pre-outburst phase in early 2006. Acosta-Pulido et al (2007) estimated the inclination angle of disc to be 61 • and also estimated the accretion rate to be 5 × 10 −6 M yr −1 during outburst and 5 × 10 −7 M yr −1 in 2006 quiescent state. Aspin et al (2006) reported that ∼ 37 years prior to 2003 outburst, i.e.…”
Section: Introductionmentioning
confidence: 99%